A Survey on Moving Object Detection and Tracking Techniques (International Journal of Engineering and Computer Science, 2017)
Moving object detection and tracking are the more important and challenging task in video surveillance and computer vision applications. Object detection is the procedure of finding the non-stationary entities in the image sequences. Detection is the first step towards tracking the moving object in the video. Object representation is the next important step to track.    Tracking is the method of identifying, the position of the moving object in the video. Identifying the position is much more challenging task then detecting the moving object in a video.  Object tracking is applied in numerous applications like in robot vision, monitoring the traffic, Video surveillance, Video in-painting and Simulation. Here we are going to present a brief review of numerous object detection, object classification and object tracking algorithms available.